The effect of greenwashing perception, green word of mouth, and green marketing on h&m purchase intentions in Jakarta - Natasya, Rasya (Teorija in praksa, 2023)
Greenwashing has long been an issue in Western and developed countries. Yet, this matter regrettably remains quite underexplored among academics in developing and emerging markets, especially in Indonesia. The presented quantitative research focuses on the impact of greenwashing perception, green word of mouth (“green WOM”) and green marketing on intentions to purchase items at H&M in Jakarta. Hypotheses were answered with the SEM-PLS model using SmartPLS3 software. Based on a questionnaire administered to 200 respondents, results show that the perception of greenwashing has a direct negative impact on consumers’ purchase intentions and an indirect negative impact through green WOM, which can be influenced by the factor of lack of concern and awareness in Jakarta. These findings stand in contrast to several studies in Europe that were used as a reference while conducting this research. At the same time, green WOM strengthens the positive impact between green marketing and purchase intentions. Practical implications for companies include taking substantial steps towards sustainability and the need to adopt a fact-based approach without embellishment
Keywords: greeen marketing; green word of mouth; greenwashing perception; nakupne namere; purchase intention; Zavajajoče oglaševanje; Zaznavanje; zaznavanje zelenega zavajanja; zeleno trženje; zeleno trženje od ust do ust